Comparative economics of Sida hermaphrodita (l.) Rusby and Silphium perfoliatum L. as bioenergy crops in Europe - Cumplido-Marin, Laura; Burgess, Paul J.; Facciotto, Gianni; Coaloa, Domenico; Morhart, Christopher; Bury, Marek; Paris, Pierluigi; Nahm, Michael; Graves, Anil (Elsevier, 2022)
The purpose of this research was to fill the identified gap on financial data of Sida hermaphrodita (L.) Rusby (Sida) and Silphium perfoliatum L. (Silphium), two perennial bioenergy crops that potentially provide a more sustainable alternative/complement to other bioenergy crops. Using discounted cash flow analysis, the Net Present Values of Sida and Silphium were compared to a rotation of other arable crops including maize, and the two energy crops of short rotation coppice and Miscanthus. The analysis was completed using the SidaTim analysis tool for the UK, Italy, Germany and Poland, producing a total of four independent models. The results showed that with no subsidies, cultivating Sida was unattractive in all four countries relative to other crop options. However, Silphium, was an economically viable option in each country. Both Sida and Silphium can offer greater environmental benefits than other arable crops, and the profitability of each crop would be further enhanced if additional payments for such public services were made to farmers, and if there were secure markets for the sale of the biomass. This study is the first comparative economic analysis in West and Central Europe of the two novel energy crops in comparison to more common energy crops and an arable rotation.
Keywords: Cup plant; Virginia fanpetals; Virginia mallow; economic analysis; production economics